Modulating the proteinase inhibitory profile of a plant cystatin by single mutations at positively selected amino acid sites - Kiggundu, Andrew; Goulet, Marie-Claire; Goulet, Charles; Dubuc, Jean-François; Rivard, Daniel; Benchabane, Meriem; Pépin, Geneviève; Vyver, Christell van der; Kunert, Karl; Michaud, Dominique (The Plant journal : for cell and molecular biology, 2006)
Cysteine proteinase inhibitors of the cystatin superfamily have several important functions in plants, including the inhibition of exogenous cysteine proteinases during herbivory or infection. Here we used a maximum-likelihood approach to assess whether plant cystatins, like other proteins implicated in host-pest interactions, have been subject to positive selection during the course of their evolution. Several amino acid sites were identified as being positively selected in cystatins from either Poaceae (monocots) and Solanaceae (dicots). These hypervariable sites were located at strategic positions on the protein: on each side of the conserved glycine residues in the N-terminal trunk, within the first and second inhibitory loops entering the active site of target enzymes, and surrounding the [smallcapital larfav] motif, a sequence of unknown function conserved among plant cystatins. Supporting the assumption that positively selected, hypervariable sites are indicative of amino acid sites implicated in functional diversity, mutants of the 8th cystatin unit of tomato multicystatin including alternative residues at positively selected sites in the N-terminal trunk exhibited highly variable affinities for the cysteine proteases papain, cathepsin B and cathepsin H. Overall, these observations support the hypothesis that plant cystatins have been under selective pressure to evolve in response to predatory challenges by herbivorous enemies. They also indicate the potential of site-directed mutagenesis at positively selected sites for the generation of cystatins with improved binding properties.